Energy for sustainability : technology, planning, policy - Randolph, John.; Masters, Gilbert M. (Washington, D.C : Island Press, 2008)
An undergraduate textbook on renewable energy and energy efficiency with a focus on the community scale. A treatment of energy sources and uses, it examines the full range of issues - from generating technologies to land use planning - in making the transition to sustainable energy.
Sect. I. Energy Patterns and Trends -- Ch. 1. The Energy Imperative and Patterns of Use -- Ch. 2. Energy Sources and Sustainability -- Ch. 3. Energy Futures -- Sect. II. Energy Fundamentals -- Ch. 4. Fundamentals of Energy Science -- Ch. 5. Energy Analysis and Life-Cycle Assessment -- Sect. III. Buildings and Energy -- Ch. 6. Energy Efficiency for Buildings -- Ch. 7. Solar Energy for Buildings -- Ch. 8. From Whole Building to Whole Community Energy -- Sect. IV. Sustainable Electricity -- Ch. 9. Centralized Electric Power Systems -- Ch. 10. Distributed Energy Resources -- Ch. 11. Photovoltaic Systems -- Ch. 12. Large-Scale Renewables : Wind and Solar -- Sect. V. Sustainable Transportation and Land Use -- Ch. 13. Transportation Energy and Efficient Vehicles -- Ch. 14. Biofuels, Biomass, and Other Alternative Fuels -- Ch. 15. Whole Community Energy and Land Use -- Sect. VI. Energy Policy and Planning -- Ch. 16. Market Transformation to Sustainable Energy -- Ch. 17. Energy Policy -- Ch. 18. U.S. State and Community Energy Policy and Planning.
Includes bibliographical references.
Keywords: RENEWABLE ENERGY SOURCES